Optimization of ammonium phosphate, potassium sulfate and Saccharomyces cerevisiae in the production of acetic acid in a batch fermentor using Response Surface Methodology - Marjan Teimorimanesh; Hajar Abbasi (مجله پژوهش‌های علوم و صنایع غذایی ایران, 2022)
[1][2]Introduction: Vinegar is an ancient fermented food consumed by human since Babylons period. It is a condiment that produced from various carbohydrate sources by alcoholic and subsequently acetic acid fermentation. Alcoholic fermentation is carried out by Saccharomyces cerevisiae, while the acetic acid fermentation is performed by acetic acid bacteria. Most of the acetic acid bacterial strains are classified in the Acetobacter genus and derived from vinegar factories that are able to oxidize ethanol to acetic acid and some strains over oxidize acetic acid into CO2 and H2O (over-oxidation). In acetic acid fermentation, important physical parameters that affect the growth of A.aceti are temperature, aeration and pH. Other most important factors for enhancing production efficiency of acetic acid are the nutrients of substrate for increases microbial activity. Considering the significant role of carbon sources and micronutrients in the fermentation culture to increase the production of acetic acid, in the present study, the effect of adding ammonium phosphate (0- 0.75 g), potassium sulfate (0- 0.75 g) and Saccharomyces cerevisiae (0- 1.5 g), were investigated to increase the production of acetic acid using Acetobacter spp. Materials and methods: Yeast (Saccharomyces cerevisae) was obtained from the Iranian Research Organization for Science and Technology, Department of Biotechnology in Tehran, Iran with code number 5052. All chemicals were from Merck Co. Acetic acid production was performed by Acetobacter spp in a fermenter (Biostat B B.Brun) with a capacity of 10 L which contained 5000 ml of fermentation culture in 9.9 acidity. Mash with a capacity of 3000 ml containing 450 ml of vinegar with 9.9 acidity, 350 ml of ethanol 97%, 2.1 g of dextrose and the rest up to 3000 ml of water was produced and 300 ml of it was injected into the fermenter every 4 hours (in 10 steps). After complete injection, the fermentation operation continued for 9 hours. Agitation speed, aeration rate and temperature in the fermenter were 900 rpm, 50 L/min and 32°C, respectively. Determination of the best conditions for producing acetic acid was performed by Response Surface Methodology (RSM) in the form of central composite design. Independent variables were yeast concentration (0- 1.5 g), concentration of the ammonium phosphate (0- 0.75 g), and the potassium sulfate concentration (0- 0.75 g). RSM models were developed and optimization was done for the highest acidity, activity and oxidation value and the lowest residual alcohol content in the product. Optimal and control samples were examined in terms of qualitative characteristics such as acidity, activity, residual alcohol content, oxidation value, total dissolved solids, reducing sugar, total phenol, ascorbic acid, sulfur dioxide and heavy metals. Comparison of the optimal and control samples was done in a completely randomized design using SAS ver: 9.1 software. Results and discussion: The results showed that increasing the concentration of yeast and ammonium phosphate led to increase the initial and final acidity, activity and oxidation value and decrease the amount of residual alcohol. The effect of increasing potassium sulfate was negative and reduced the initial and final acidity, activity and oxidation value. However, interaction effects of potassium sulfate concentration with other variables at its intermediate levels on reducing the amount of residual alcohol in the product was positive. The optimal levels of the studied variables were determined as 1.5 g of Saccharomyces cerevisiae, 0.75 g of ammonium phosphate and 0.38 g of potassium sulfate. In control sample (without the independent variables), initial and final acidity, activity and oxidation index were lower and the residual alcohol content was higher than the standard level. Therefore, the optimal sample was compared with the control and using industrial activator (Astasome). The optimal sample in terms of initial and final acidity, activity, residual alcohol content and oxidation value had not a significant difference (p> 0.05) with the control sample (containing Astasome). Moreover, the optimal and control samples were not significantly difference in ascorbic acid and reducing sugar (p> 0.05), while the optimal sample in terms of total phenol content, sulfur dioxide and heavy metals like lead, zinc and copper was superior compared to the control sample (p <0.05). Overall, the results of this study indicated the positive effect of yeast, ammonium phosphate, and the potassium sulfate at suitable concentration on qualitative characteristics of acetic acid.The results revealed that using of appropriate amounts of Saccharomyces cerevisiae, ammonium phosphate and potassium sulfate in substrate as a source of micronutrients improve quality of acetic acid production by Acetobacter spp.